Estimativas do investimento microrregional por meio de variáveis proxies de crédito público: Fundos constitucionais de financiamento e BNDES (2002-2019) - Raphael de Oliveira Silva; Aristides Monteiro Neto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– The study aims to estimate amounts of investment in the geographic microregions of the North, Northeast and Midwest regions, the preferred territorial scale of the National Regional Development Policy (PNDR). To this end, it is fundamentally based on series of public credit data from regional development banks - Banco da Amazônia (Basa), Banco do Nordeste (BNB), and Banco do Brasil (BB) for the Midwest region - alongside the disbursements from the National Bank for Economic and Social Development (BNDES) to those microregions. The data coverage period is 2002 to 2019. The estimates elaborated allow identifying and evaluating the direction - in the territory and over the last two decades - taken by the resources of the main public development banks of the country. Thus, becoming a mechanism for identifying investment spending flows and reorienting trajectories as well as mitigating the concentrating effects of enterprises stimulated by regional policy.
10419/284882
Keywords: O18; R11; R58; 330; microregional investment; public credit sources; regional policy